Effect of Strategic Planning, Business Innovation, Digital Transformation, and Organisational Agility on Competitive Advantage of Modern Service Companies in West Java - Chaerunnisa Chaerunnisa; Ratih Hurriyati; Heny Hendrayati; Puspo Dewi Dirgantari (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The increasingly dynamic business environment compels modern service companies to continuously strengthen their competitive advantage. Despite extensive studies on strategic and digital capabilities, empirical research that simultaneously integrates strategic planning, business innovation, digital transformation, and organisational agility—particularly within the modern service sector—remains limited. This study aims to examine the effects of these four strategic factors on the competitive advantage of modern service companies in West Java Province. This research adopts a quantitative causal approach using a survey method. Data were collected from 134 managers of modern service companies across financial services, tourism, transportation, education, and information and communication technology sectors. The data were analysed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with SmartPLS software. The results indicate that strategic planning, digital transformation, and organisational agility have positive and significant effects on competitive advantage. Conversely, business innovation exhibits a significant negative effect, suggesting that innovation initiatives that are not strategically aligned or organisationally prepared may undermine competitiveness in service-oriented firms. The model demonstrates strong explanatory power, with the independent variables jointly explaining a substantial proportion of the variance in competitive advantage. This study contributes to strategic management literature by providing empirical evidence on the differentiated roles of strategic, digital, and organisational capabilities in shaping competitive advantage within the modern service sector. Practically, the findings highlight the importance of prioritising strategic clarity, adaptive capability, and purposeful digitalisation, while managing innovation selectively to ensure alignment with organisational readiness and market needs. Keywords: strategic planning; business innovation; digital transformation; organisational agility; competitive advantage; modern service companies